MOTHER'S KNOWLEDGE ABOUT LACTATION AMENORRHEA METHOD (LAM) OF BREASTFEEDING - Ninik Azizah; Vivin Eka Rahmawati; Siti Roudhotul Jannah; Suyati Suyati; Zulfa Khusniyah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: To Assess the Level of Knowledge of Breastfeeding Mothers About the Lactation Amenorrhea Method (LAM).Methods: Description research with a population of 75 respondents and sampling of all breastfeeding mothers. The data analysis used is univariate analysis.Results: Most of the respondents were aged between 26-35 years (73.3%), more than half of them had their last education at the upper secondary level (50.7%), most of the respondents were unemployed (72%), the most parity was primigravida (68%), all respondents had been exposed to information about LAM (100%) which was mostly sourced from electronic media (92%) and most respondents had sufficient knowledge about LAM (40%) .Conclusion:Â Most of the respondents have sufficient knowledge. Therefore, the role of health workers is needed to further intensify information about lactational amenorrhea contraceptive methods so that they can use them correctly.